PERHITUNGAN ANGGARAN BIAYA TENAGA KERJA LANGSUNG PADA PT. ANEKA SUMBER TATA BAHARI DI DESA TULEHU - Tahalua, Inda Sari; Tupamahu, Kevin H; Tomasoa, Theodora Florence (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
This research aims to find out how to prepare the direct labor cost budget calculation at PT. Various Sources of Maritime Management in Tulehu Village in January-March 2024. To find out the calculation of the direct labor cost budget at PT. The Sumber Tata Bahari annex requires production data at PT. ASTB and working hours data wage/hour rates. The method used in this research is a qualitative method. The results of the research can be seen from the preparation of the company's direct labor cost budget with theoretical studies that are appropriate, where, based on the calculation results, a direct labor cost budget for each employee can be obtained, fish washing production for each month of January is IDR 37,125,000, divided by 15 employees the result is IDR 2,475,000 per person, in February IDR 38,610,000 divided by 15 employees the result is amounting to IDR 2,574,000 per person, and whereas in March IDR 37,125,000 was divided by 15 employees the result is IDR 2,475,000 per person. So one person's income for 3 months is IDR 7,524,000, while the total wage during the first quarter is IDR 112,860,000. with results that have been calculated in accordance with company regulations with total wages for 15 employees amounting to IDR 112,860,000 for the 3 quarter periods January-March 2024 at PT. ASTB.